(untitled) (Sebha University Conference Proceedings, 2024)
Thyroid hormones have a role in the growth and development of all body tissues, which have significant effects on oxygen consumption and metabolic rate. In this study, aqueous extracts of both ginger (Zingiber officinale) and a suspension of palm pollen (Phoenix dactylifera) were evaluated on weight changes in rats with propylthiouracil (PTU)-induced hypothyroidism. Thirty rats were used, their weights ranged between (190-220g). Divided into two experiments, the first experiment contained five groups, with 6 male rats for each group. The first group was the negative control (normal), which was not treated with anything, the second was the positive control (infected), which received PTU at a dose of 10mg/kg of body weight. The third group was dosed with the aqueous extract of ginger at a concentration of 24mg/kg with PTU, the fourth group was given orally the aqueous suspension of palm pollen at a dose of 120mg/kg of body weight with PTU, and the fifth group was dosed with both extracts (ginger and palm pollen) with PTU for four weeks. Body weights and reproductive organs were measured. The results showed a significant decrease (p value < 0.05) in the body weight in the infected group compared to the normal group, the body weight increased in groups (fourth and five) compared to the infected group and the third group. The weight of the reproductive organs increased in all groups treatment with extracts (third, fourth, and fifth) compared to the infected group.